A CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, a preparation method thereof, and a performance evaluation method thereof

By introducing an elastomer layer into the skin of the CFRP-honeycomb aluminum sandwich structure, the problem of insufficient impact resistance under impact is solved, and higher impact resistance and more uniform matrix damage are achieved.

CN118849549BActive Publication Date: 2025-04-11HARBIN INST OF TECH AT WEIHAI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410896181.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2025-04-11
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

The existing CFRP-honeycomb aluminum sandwich structure lacks impact resistance under impact, especially the brittleness of the skin, resulting in a significant reduction in the residual strength of the material.

Method used

An appropriate proportion of elastomer layers were introduced between different upper skins of CFRP-honeycomb aluminum or between different upper skins of the lower skins. The elastomer layer was inserted into the skin structure by a preparative method, and its impact resistance was evaluated by a performance evaluation method combined with simulation and experiment.

Benefits of technology

The impact resistance of the CFRP-honeycomb aluminum sandwich structure is improved, especially the damage impedance is significantly improved under large impact energy. The introduction of the elastomer layer makes the impact load distribution more widely, the material utilization rate is improved, the stratification phenomenon is reduced, and the matrix failure is more uniform.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118849549B_ABST
    Figure CN118849549B_ABST
Patent Text Reader

Abstract

The present invention discloses a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, comprising: inserting an elastomer between 0°C FRP and 90°C FRP of different layers of an upper skin or / and between 0°C FRP and 90°C FRP of different layers of a lower skin in the CFRP-honeycomb aluminum; compared with a traditional CFRP / honeycomb aluminum sandwich structure, the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer provided by the present invention has higher impact resistance, especially the damage impedance under large impact energy is greatly improved; the present invention also discloses a preparation method and a performance evaluation method of the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, and compares the impact performance by using experimental and numerical methods, and explains the difference and the influence of the elastomer on the impact damage mechanism of the sandwich structure from the perspective of impact damage mechanism and energy distribution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the research field of composite materials, and in particular to a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, a preparation method thereof, and a performance evaluation method thereof. Background Art

[0002] Composite sandwich structures have received great attention and research in the academic and industrial fields due to their excellent fatigue and impact resistance, and are widely used in aerospace, automotive, shipbuilding and other fields. Therefore, it is very necessary to conduct innovative research on this structural material to further improve its mechanical properties.

[0003] As a flexible material, elastomers can help improve the brittle characteristics of traditional lightweight and high-strength materials, providing great potential for improving the mechanical properties of advanced lightweight materials. This elastomer material is often introduced into carbon fiber composite laminates to improve the toughness of the laminates and increase damage resistance.

[0004] During the research on the sandwich structure of CFRP skin, we found that there was no relevant research on the introduction of elastomers into the CFRP skin of this structure to toughen this type of material to improve its impact resistance, even though the conclusion that the introduction of elastomers into traditional lightweight and high-strength materials can significantly improve the impact resistance has been confirmed. Summary of the invention

[0005] The present invention designs and develops a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer. The purpose of the present invention is to introduce an appropriate proportion of elastomer layers into different areas of the skin to improve the impact resistance.

[0006] The present invention also designs and develops a method for preparing a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer. The purpose of the invention is to solve the preparation problem of inserting an elastomer into the existing pure skin CFRP-honeycomb aluminum sandwich structure.

[0007] The present invention also designs and develops a performance evaluation method for a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer. The purpose of the present invention is to provide an impact resistance evaluation method based on a combination of simulation and experiment.

[0008] The technical solution provided by the present invention is:

[0009] A CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, comprising:

[0010] An elastomer is inserted between the 0°C FRP and the 90°C FRP of different layers of the upper skin or / and between the 0°C FRP and the 90°C FRP of different layers of the lower skin in the CFRP-honeycomb aluminum.

[0011] Preferably, an elastomer is inserted between the second CFRP layer and the third CFRP layer, and between the fifth CFRP layer and the sixth CFRP layer of the upper skin in the CFRP-honeycomb aluminum.

[0012] A method for preparing a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer comprises the following steps:

[0013] Step 1, using unidirectional CFRP prepreg to orthogonally lay up the upper skin and the lower skin, in the process of laying up the upper skin and the lower skin, inserting an elastomer between the 0°C FRP and the 90°C FRP of different layers of the upper skin or / and between the 0°C FRP and the 90°C FRP of different layers of the lower skin as needed;

[0014] Step 2, curing the skin with the elastomer inserted separately;

[0015] Step 3: Connect the cured skin, the honeycomb aluminum core and the uncured skin by means of an epoxy resin film and then cure them to obtain the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer.

[0016] A performance evaluation method for a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer comprises the following steps:

[0017] Step 1, performing multiple groups of energy impact preliminary experiments on the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer and the pure CFRP-honeycomb aluminum sandwich structure to determine the impact energy range;

[0018] Step 2: performing a low-speed impact test on the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer within the impact energy range, and establishing a simulation model under low-speed impact;

[0019] Step three: compare the simulation model with the experimental results of the low-speed impact test, obtain multiple performance parameters, determine the feasibility of the simulation model, and evaluate the performance of the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer based on the performance parameters.

[0020] Preferably, in step three, the performance parameters include a load history curve, a macroscopic image after impact, a microscopic image after impact, a plastic energy-displacement curve, a crack energy-displacement curve, a stratification image after impact, an intra-layer damage image after impact, and an energy distribution curve during the impact process.

[0021] Preferably, the load history curve includes a load-time curve, a load-displacement curve and an energy-time curve.

[0022] Preferably, the post-impact intra-layer damage image includes matrix failure images of different plies of the CFRP panel after impact and energy dissipation images of different CFRP plies.

[0023] Preferably, the impact energy ranges from 8J to 15J.

[0024] Preferably, the low-speed impact test in step 2 includes the following process: clamping the sample to be impacted in a fixture, and using an impactor with a spherical hammer head mass of 5 kg and a spherical hammer head diameter of 16 mm to impact the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer with a preset energy;

[0025] The preset energies include 10J and 15J, and the impact speed is no more than 3.4m / s.

[0026] Preferably, in step 3, performing performance evaluation includes:

[0027] The onset of damage to the CFRP-aluminum honeycomb sandwich structure containing the elastomer layer is evaluated by the appearance of oscillations in the load history curve;

[0028] In the macroscopic image after the impact, the impact energy is evaluated by the deformation of the upper skin and the degree of compression and buckling of the middle honeycomb aluminum;

[0029] evaluating the impact energy by the damage of the upper skin in the microscopic image after the impact;

[0030] The fracture condition of the honeycomb aluminum in the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer is evaluated by the appearance of a steep drop in the plastic energy-displacement curve;

[0031] The fracture condition of the upper skin in the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer is evaluated by the appearance of a steep drop in the crack energy-displacement curve;

[0032] Determining and evaluating the effect of introducing the elastomer into the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer on reducing the delamination by the delamination condition in the delamination image after the impact;

[0033] evaluating the degree of matrix damage by the ratio of matrix cracking areas in the matrix failure images of different plies of the CFRP panel after impact and the energy dissipation images of the different CFRP plies;

[0034] The overall load-bearing capacity is evaluated by the energy distribution in the energy distribution curve during the impact.

[0035] The beneficial effects of the present invention are:

[0036] 1. The present invention introduces an elastomer layer in an appropriate proportion into the traditional pure CFRP skin honeycomb aluminum sandwich core structure according to the application scenario and mechanical performance requirements to improve its impact resistance, and uses experimental and numerical methods to compare the impact performance of the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer and the honeycomb aluminum sandwich core structure of pure CFRP skin, and explains this difference and the influence of the elastomer on the impact damage mechanism of the sandwich structure from the perspective of impact damage mechanism and energy distribution;

[0037] 2. Compared with the traditional pure CFRP skin honeycomb aluminum sandwich core structure, the CFRP-honeycomb aluminum sandwich structure with an elastomer layer provided by the present invention has higher impact resistance, especially the damage impedance under large impact energy is greatly improved. The introduction of the elastomer layer distributes the load near the impactor to a larger area, so more materials participate in elastic energy absorption, and the material utilization rate is improved with a smaller amount of damage. The delamination phenomenon between CFRP and aluminum and between 0° and 90° CFRP is reduced, the matrix damage distribution is larger, more dispersed, and more uniform, and the plastic deformation of the honeycomb aluminum is also reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1a This is a schematic diagram of the honeycomb aluminum sandwich core structure with pure CFRP skin according to the present invention.

[0039] Figure 1b This is a schematic diagram of a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer in the upper skin of the present invention.

[0040] Figure 2 Schematic diagram of finite element simulation and experimental results of the pure CFRP skin honeycomb aluminum sandwich structure and the upper skin CFRP-honeycomb aluminum sandwich structure containing an elastomer layer under 10J and 15J impacts according to the present invention ( Figure 2 a is the load-time curve of the pure CFRP skin honeycomb aluminum sandwich structure under 10J impact; Figure 2 b is the load-displacement curve of the honeycomb aluminum sandwich structure with pure CFRP skin under 10J impact; Figure 2 c is the energy-time curve of the honeycomb aluminum sandwich structure with pure CFRP skin under 10J impact; Figure 2 d is the load-time curve of the honeycomb aluminum sandwich structure with pure CFRP skin under 15J impact; Figure 2 e is the load-displacement curve of the pure CFRP skin honeycomb aluminum sandwich structure under 15J impact; Figure 2 f is the energy-time curve of the pure CFRP skin honeycomb aluminum sandwich structure under 15J impact; Figure 2 g is the load-time curve of the upper skin, which is a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, under a 10J impact; Figure 2 h is the load-displacement curve of the upper skin, which is a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, under a 10J impact; Figure 2 i is the energy-time curve of the upper skin, which is a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, under a 10J impact; Figure 2 j is the load-time curve of the upper skin, which is a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, under a 15J impact; Figure 2 k is the load-displacement curve of the upper skin, which is a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, under a 15J impact; Figure 2 l is the energy-time curve of the upper skin, which is a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, under a 15J impact).

[0041] Figure 3 Cross-sectional views along the length direction of a honeycomb aluminum sandwich structure with pure CFRP skin and a CFRP-honeycomb aluminum sandwich structure with or without an elastomer layer after impact of different energies.

[0042] Figure 4 Microscopic slices of the CFRP-honeycomb aluminum sandwich structure with an elastomer layer along the length direction after impact ( Figure 4 a is a microscopic section of a pure CFRP skinned aluminum honeycomb sandwich structure under 10J impact; Figure 4 b is a microscopic section of the upper skin, which is a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, under a 10J impact; Figure 4 c is a microscopic section of a pure CFRP skinned aluminum honeycomb sandwich structure under 10J impact; Figure 4 d is a microscopic section image of the upper skin, which is a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, under a 10J impact).

[0043] Figure 5a A load-displacement curve diagram of deformation of honeycomb aluminum in the honeycomb aluminum sandwich structure with pure CFRP skin described in the present invention.

[0044] Figure 5b The upper skin described in the present invention is a load-displacement curve diagram of deformation of honeycomb aluminum in a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer.

[0045] Figure 6a The crack energy inside the sandwich structure in the pure CFRP skin honeycomb aluminum sandwich structure described in the present invention.

[0046] Figure 6bThe upper skin described in the present invention is a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, and the crack energy inside the sandwich structure.

[0047] Figure 7a A diagram showing the layering of the sandwich structure of the pure CFRP skinned aluminum honeycomb sandwich structure of the present invention.

[0048] Figure 7b The upper skin described in the present invention is a sandwich structure layering diagram of a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer.

[0049] Figure 8a The matrix of different layers of CFRP panels in the pure CFRP skinned aluminum honeycomb sandwich structure of the present invention fails.

[0050] Figure 8b The upper skin described in the present invention is a matrix failure of different layers of CFRP panels in a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer.

[0051] Figure 8c It is the energy dissipated by each layer of CFRP in the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer and the honeycomb aluminum sandwich core structure with pure CFRP skin described in the present invention.

[0052] Fig. 9 The energy distribution of the traditional sandwich structure and the novel sandwich structure described in the present invention during the impact process is compared. DETAILED DESCRIPTION

[0053] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0054] The present invention provides a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer. The impact resistance of the traditional pure CFRP skin honeycomb aluminum sandwich core structure is insufficient and the rigidity is too high, so a new design is needed to improve it. In view of the improvement requirements, an appropriate proportion of elastomer layers are introduced at different positions of the upper and lower CFRP skins or the single-sided CFRP skins, and the optimization design is performed to determine the appropriate elastomer introduction method and specific design; as a preferred embodiment, in this embodiment, the traditional pure CFRP skin honeycomb aluminum sandwich core structure skin is redesigned, and an elastomer layer is introduced between the 0°C FRP and 90°C FRP of the upper or lower skin. The position and number of the elastomer layer should be selected according to the actual material application scenario, and are also related to the mechanical property requirements of the target material.

[0055] The design of introducing elastomers into the skin of the traditional pure CFRP skin honeycomb aluminum sandwich core structure is because the existing pure CFRP skin of this type of material is thin and hard, and is extremely susceptible to impact damage. For example, various low-speed impacts can cause brittle damage to the skin, and the residual strength of the material is significantly reduced. As a flexible material, elastomers are often used to improve the brittle characteristics of traditional lightweight and high-strength materials, which just fits the requirements for toughening the pure CFRP skin honeycomb aluminum sandwich core structure to improve its impact resistance.

[0056] The present invention also provides a method for preparing a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, wherein two materials are prepared by a co-bonding method, and the actual verification of the design is carried out. A certain elastomer introduction scheme is selected to prepare a CFRP-honeycomb aluminum sandwich structure sample containing an elastomer layer, and a control group of honeycomb aluminum sandwich core structure samples with pure CFRP skins are prepared. First, the CFRP prepreg is orthogonally laid, and an elastomer layer is added during the laying process according to a specific design. After the prepreg laying of the skin with the elastomer is completed, the skin with the elastomer is first cured separately. After the curing is completed, the uncured (i.e., no elastomer is added) skin and honeycomb aluminum core are connected with an epoxy resin film, and then cured to obtain a complete sample, which is finally cut into experimental samples of a predetermined size.

[0057] The present invention provides a method for evaluating the impact resistance of a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, comprising the following steps:

[0058] Step 1: Conduct a preliminary experiment, and conduct multiple energy impacts on the CFRP-honeycomb aluminum sandwich structure with an elastomer layer and the honeycomb aluminum sandwich structure with pure CFRP skin to determine the appropriate impact energy range for the final experiment. After determining the appropriate impact energy through the preliminary experiment, set up a low-speed impact test control of the two materials at different energies. Conduct several groups of the same type of samples in each energy group to ensure consistency, and collect experimental data such as load-time curves, load-displacement curves, and energy-time curves;

[0059] Step 2. Use ABAQUS2021 software to study the impact behavior of CFRP-honeycomb aluminum sandwich structures containing elastomer layers and pure CFRP-honeycomb aluminum sandwich structures under low-speed impact. Establish a simulation model consisting of an impactor with an initial velocity corresponding to the actual experiment and a CFRP / honeycomb aluminum sandwich structure of the same size. Regarding the modeling method, the grid offset method is mainly used to establish the upper and lower skins of the model, and a sensitivity analysis of the grid size is performed to save computing power as much as possible while ensuring the accuracy of the model. The constraint method in this model also adopts the same constraint method as in the actual experiment, and by changing the speed of the impactor, different impact energies are simulated under the premise of considering the acceleration of gravity;

[0060] Step 3: Get the simulation model, simulate the energy corresponding to the experimental energy, and compare the results with the experimental data to determine the correctness and feasibility of the simulation model. After determining the credibility and feasibility of the model, combine the simulation model and experimental data to facilitate subsequent damage mechanism and energy research;

[0061] Step 4: Starting from the load history curve of the experimental simulation results, compare the load changes of the two materials during the impact process. With the help of the performance of the load history curve, analyze and compare the internal damage form and degree during the impact process, and study the changes in mechanical properties and damage modes caused by the introduction of elastomers into the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer.

[0062] The samples after impact were observed macroscopically and microscopically, and damage manifestations such as fiber breakage and delamination damage of the two materials after low-speed impact were collected and compared with simulation experimental data to evaluate the performance of the two materials.

[0063] Starting from the change of plastic strain energy, matrix damage, fiber fracture and delamination, the performance of the two materials was evaluated through various damage conditions obtained through experimental observation and the plastic deformation absorption energy under the corresponding energy simulated in the simulation model, delamination damage of different layers of CFRP, energy dissipation within the layer and stress distribution.

[0064] During the impact process, the kinetic energy of the impactor is mainly transferred to the sandwich structure through damage energy and elastic strain energy. The amount of load-bearing materials involved in the structure directly affects the degree of damage to the sandwich structure. Therefore, it is necessary to study the energy distribution of this type of material during low-speed impact, and then explain the similarities and differences between its damage mechanism and traditional materials, and to evaluate the performance of this new material.

[0065] Example

[0066] The design of introducing elastomers into the skin of the honeycomb aluminum sandwich core structure of the traditional pure CFRP skin is because the existing pure CFRP skin 110 of this type of material is thin and hard, and is very susceptible to impact damage. For example, various low-speed impacts can cause brittle damage to the skin, and the residual strength of the material is significantly reduced. As a flexible material, elastomers are often used to improve the brittle characteristics of traditional lightweight and high-strength materials, which just fits the requirements for toughening the honeycomb aluminum sandwich core structure of the traditional pure CFRP skin to improve its impact resistance.

[0067] According to the actual application scenario, the position and proportion of the elastomer layer can be adjusted to meet different mechanical properties and impact resistance requirements and adapt to various scenarios. The specific design scheme after introduction in this example is a scheme selected to meet the verification requirements of this idea. Those skilled in the art can reasonably select the position to add the elastomer according to needs.

[0068] In this embodiment, a traditional pure CFRP skin honeycomb aluminum sandwich structure is used as the basis. Figure 1b As shown, in the structure, an elastomer layer 130 is inserted between different layers of unidirectional CFRP on the upper skin 110, and the specific design is to insert the elastomer layer between the second layer, the third layer, the fifth layer, and the sixth layer. The overall structure of the upper skin is

[0069] The method for impact resistance evaluation provided by the present invention is an evaluation method based on experimental characterization and simulation, and is specifically as follows:

[0070] 1. Design of low-speed impact drop hammer experiment and sample preparation:

[0071] 1. According to the material design plan and preliminary experimental design, the experimental samples are made. The types of samples are as follows:

[0072] (1) Figure 1a As shown, the pure CFRP skin honeycomb aluminum sandwich structure includes a skin 110 and a honeycomb aluminum 120 .

[0073] (2) Figure 1b As shown, the upper skin is a honeycomb aluminum sandwich structure of a CFRP skin containing an elastomer, including a skin 110 , a honeycomb aluminum 120 and an elastomer 130 .

[0074] Sample preparation steps and details:

[0075] The UD prepreg (provided by Weihai Guangwei Composite Materials Co., Ltd.) is unidirectional USN15000, which is composed of a fast-curing epoxy resin matrix and a high-strength carbon fiber bundle. The fiber area weight of the unidirectional carbon fiber prepreg is 150g / m 2 , the resin weight content is 38%, and the nominal thickness of a single layer is 0.15 mm.

[0076] The commercial name of the elastomer layer used in this embodiment is Kraibon (provided by Gummiwerk KRAIBURG GmbH & Co. KG), the batch number is AA9CFZ, and the density is 1090 kg / m 3, with high elongation at break, excellent weather resistance, often used in impact applications, the mixture is an ethylene propylene diene monomer (EPDM) rubber elastomer, which facilitates good adhesion to the different CFRP layers, the elastomer is supplied in a pre-cured state and vulcanized in the same process step as the CFRP, the elastomer layer thickness is 0.35mm. The engineering stress-strain curve of the quasi-static tensile test was provided by KRAIBURG.

[0077] The honeycomb aluminum used in the present invention is 5052 series aluminum alloy with a density of 2760kg / m 3 The height h of the cell of the honeycomb core is 20 mm, the side length a is 3 mm, and the single-layer wall thickness t is 0.05 mm.

[0078] Take the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer as an example: the upper skin is orthogonally stacked with unidirectional CFRP prepreg, and in this process the elastomer layer is laid between the 2nd and 3rd layers, and the 5th and 6th layers of CFRP prepreg according to the design, and then the laid upper skin is placed alone in a vacuum bag and cured in a curing furnace; in this process, the curing temperature is set to rise stepwise to 120 degrees Celsius, 1.97MPa, and the temperature is maintained for 90 minutes to allow the skin to be fully cured, and then the temperature is lowered to 50 degrees Celsius after the curing is completed before taking out the upper skin.

[0079] Subsequently, a co-bonding process was adopted to connect the cured upper skin, honeycomb aluminum and uncured lower skin with epoxy resin film according to the design and seal them with a vacuum bag before curing. The curing temperature and pressure were the same as the curing conditions of the upper skin alone, eventually forming a complete CFRP-honeycomb aluminum sandwich structure containing an elastomer layer.

[0080] Cut the samples into uniform sizes of 150mm×100mm and mark the geometric center of the upper surface as the impact point.

[0081] 2. Design detailed drop hammer test:

[0082] (1) Preliminary experiments were conducted on two groups of samples to determine that the impact energy range is 8J to 15J. That is, it is more reasonable to conduct low-speed impact experiments with larger and smaller energies in this energy range;

[0083] (2) Determine multiple groups of impact energies, as shown in Table 1, to form a comparison;

[0084] Table 1 Impact energy parameters

[0085]

[0086]

[0087] 3. Conduct impact test and collect data: The experiment is carried out using a drop hammer impact device. The impact device model is Zwick Roell HIT230F. The device mainly includes a 5.97kg steel hemispherical impactor, a piezoelectric sensor, an acceleration and velocity sensor, a fixture, an anti-secondary impact device, etc.

[0088] The cut 150mm×100mm sample is clamped in the fixture, and the preset energy impact is performed by adjusting the impactor height. During the impact process, the impact position is the geometric center of the upper skin, and after the first impact, the moment the impactor rebounds and leaves the panel, the anti-secondary impact device is activated to prevent a secondary impact.

[0089] The main data collected and processed are as follows:

[0090] (1) Load-time history during impact;

[0091] (2) Kinetic energy-time history of the impact process;

[0092] (3) Load-displacement history.

[0093] 2. Establish and verify the corresponding simulation model:

[0094] The impact behavior of the CFRP / honeycomb aluminum sandwich structure described in the present invention under low-speed impact is studied using ABAQUS2021 software. The established finite element model consists of an impactor with an initial velocity and a CFRP / honeycomb aluminum sandwich structure. The modeling method of offset isolated grid is adopted to establish a shell model and divide the grid, and then create an isolated grid. The grid is offset on the new isolated grid, and the two-dimensional grid is swept and stretched to generate a three-dimensional solid grid, which is generated according to the actual model.

[0095] In the sandwich structure model without elastomer, SC8R type units are used for intra-layer modeling of CFRP skin, and COH3D8 units are used for inter-layer modeling of CFRP in different ply directions, CFRP skin and honeycomb aluminum. Honeycomb aluminum is modeled using the plug-in S4R unit. After completing the modeling of CFRP skin and honeycomb aluminum, Tie connection is used to connect the skin and honeycomb aluminum, and the Cohesive unit in contact with the upper skin and honeycomb aluminum is bound to the honeycomb aluminum node. In the CFRP-honeycomb aluminum sandwich structure model with an elastomer layer, the modeling method is exactly the same as that of the honeycomb aluminum sandwich core structure with pure CFRP skin without elastomer. When modeling the upper skin, the grid offset process is offset at the position of the actual elastomer layer to form an elastomer layer, and the elastomer material parameters are assigned. The impactor is simulated as a rigid body in the gravity field, and the kinematic contact method is used to simulate the contact between the impactor and the sandwich structure, μ = 0.3. The boundary conditions were designed according to the actual experimental conditions. The displacement in the z direction was limited to the supporting area of ​​the supporting window and the clamping area of ​​the four clamps. At the same time, the rotational freedom of the four shelf clamping areas along the x, y, and z axes was also limited.

[0096] Subsequently, by adjusting the speed of the impactor, the low-speed impact conditions under different energies were simulated and compared with the experimental results under the corresponding energies. The damage condition, load history curve, load displacement curve, energy curve, etc. were compared to verify that the model has the accuracy and feasibility that meet the requirements.

[0097] In the simulation model of this embodiment, the material parameters and simulated mechanical properties in the following material model are used to establish the simulation model and verify its feasibility and accuracy.

[0098] 1. CFRP model

[0099] The intra-laminar mechanical behavior of the CFRP material was simulated using a linear orthotropic elastic model. It is important to note that the material model does not take into account the strain rate sensitivity of the composite material. This is evidenced by the fact that carbon fibers are strain rate insensitive to the dynamic properties of composite laminates. Furthermore, the impact velocity in the present invention is no greater than 3.4 m / s, which is a much lower strain rate than would be expected if a significant change in strength were to occur. The viscoelasticity of the CFRP is negligible compared to the viscoelastic contribution of the elastomer.

[0100] The Hashin theory is used as the initiation criterion for damage within the CFRP layer. Four different damage initiation mechanisms are considered, namely fiber tension, fiber compression, matrix tension, and matrix compression. Failure under these modes is initiated in the following analytical form.

[0101] Fiber tensile failure

[0102] Fiber compression failure

[0103] Matrix tensile failure

[0104] Matrix compression failure

[0105] In the formula, is the damage index of each damage mechanism, is the effective stress tensor, X T , X C is the longitudinal tensile and compressive strength, Y T , Y C is the transverse tensile and compressive strength, S L ,S T is the longitudinal and transverse shear strength, and α is the coefficient that determines the contribution of shear stress to fiber tensile failure. The elasticity and strength values ​​of CFRP are derived from the results of quasi-static tests.

[0106] The Continuum Damage Mechanics (CDM) method is used to capture the damage evolution behavior. The damage evolution model is a band mode specific fracture energy The parameters of the studied CFRP materials are shown in Table 2.

[0107] Table 2 CFRP material parameters

[0108]

[0109] 2. Elastic body model

[0110] As a typical hyper-viscoelastic material, rubber has a nonlinear time-varying constitutive relation. The strain energy function is defined using the phenomenological Malow model.

[0111] Where U is the strain energy per unit volume, U dev is the partial differential part, U vol is the volume part, is the first partial differential strain invariant, J el is the volume ratio. Deviation part U dev Calculated directly from experimental data. For compressible properties, the volume part U vol Defined as Poisson's ratio 0.475.

[0112] 3. Aluminum Model

[0113] The mechanical response of aluminum can be divided into three stages: elastic deformation, plastic hardening and fracture. For the elastic phase, the generalized Hooke's law is used. The Johnson-Cook (JC) model is used to simulate the plastic hardening and strain rate-dependent failure of aluminum. The JC model defines the yield stress as

[0114] In the formula, A, B, C, n, is the material parameter, is the equivalent plastic strain, is the equivalent plastic strain rate. The values ​​of A, B, and n are obtained from tensile tests. The constant C reflects the effect of strain rate on aluminum, and its value is 0.0083. The dynamic JC failure criterion is used to predict the failure using the effective plastic failure strain.

[0115]

[0116] Where d1-d4 are material failure parameters, p is pressure stress, and q is Mises stress. The values ​​of JC failure parameters in this finite element model are referenced and modified.

[0117] A linear progressive damage model is used to describe the damage evolution process of aluminum. Hillerborg proposed a fracture energy method to avoid damage localization. Defined as

[0118] Where σ y0 is the ultimate stress, is the equivalent plastic displacement at failure. The material parameters of aluminum are shown in Table 3.

[0119] Table 3 Material model parameters of aluminum

[0120]

[0121] 4. Hierarchical Model

[0122] The cohesive zone model (CZM) is used to capture the delamination damage between 0° and 90°FRP, between aluminum and CFRP, and between elastomer and CFRP. The traction-separation model initially assumes linear elastic behavior, followed by the initiation and evolution of damage. The elastic properties are represented by the elastic constitutive matrix

[0123]

[0124] Where t is the nominal traction stress vector, which consists of three components t n , t s , t t They represent three deformation modes: normal deformation and two out-of-plane shear deformations. n ,K sand K t and the relative displacement component δ n ,δ s ,δ t It is related to the respective deformation modes. The quadratic interaction function is used as the damage initiation criterion:

[0125]

[0126] In the formula They represent the nominal stress peak values ​​when pure separation occurs along the three deformation modes.

[0127] If damage occurs, upon further loading, the scalar damage variable D d Evolves monotonically from 0 to 1. Linear softening behavior is selected after damage occurs. The Benzeggagh-Kenane fracture criterion is used to describe the mixed mode fracture energy.

[0128]

[0129] In the formula and is the critical fracture energy when deformed purely in three directions. η is the material parameter. There is no delamination phenomenon between the aluminum and elastomer, and between the elastomer and CFRP interfaces, so these interfaces are not modeled for failure. The material model parameters of the CFRP interlayer are shown in Table 4. Because the bonding strength between honeycomb aluminum and carbon fiber reinforced plastic is lower than the interface strength between different carbon fiber reinforced plastic layers, the interface strength The same elastic properties are used for the interfaces between aluminum and CFRP and between the 0° and 90°F FRP layers.

[0130] Table 4 CFRP interlayer parameters

[0131]

[0132] 3. The damage mechanism and performance improvement of the structural design are evaluated by combining the simulation model and experimental results.

[0133] 1. Load history evaluation

[0134] like Figure 2As shown in a~2l, according to the load history curves in the drop hammer impact test results and simulation results, the onset of internal damage can be identified by the appearance of oscillations in the curves. In the simulation and experimental load history curves with an impact energy of 10J, before the load reached the peak, the sandwich structures of both skins showed slight load oscillations, which is considered to be the beginning of CFRP delamination or matrix cracking. The damage of the honeycomb aluminum sandwich structure with pure CFRP skin occurred at about 2800N. The introduction of the elastomer layer increased the damage starting load of the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer by about 29%, and the peak load of the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer increased by 16%. When the impact energy was 15J, the load of the honeycomb aluminum sandwich structure with pure CFRP skin dropped sharply to a lower value after reaching the peak load, which may be due to catastrophic damage such as fiber breakage of the upper CFRP panel, while the sandwich structure with CFRP skin containing the elastomer layer did not show a sharp drop in peak load, and the peak load increased by about 40%.

[0135] Each damage mode contributes to the total absorbed energy of the sandwich structure. From the energy-time curve, under the impact energy of 15J, the CFRP skin with an elastomer layer has less damage inside the sandwich structure than the pure CFRP skin. The final absorbed energy of the CFRP-honeycomb aluminum sandwich structure with an elastomer layer is 30% lower than that of the honeycomb aluminum sandwich core structure with a pure CFRP skin. In short, for both impact energies, the elastomer plays a positive role in increasing the initial damage load, peak load, and impact damage resistance of the sandwich structure.

[0136] 2. Macroscopic and microscopic observation and evaluation of impact test specimens

[0137] like Figure 3 As shown in the figure, the impact center of the sandwich structure after impact was macroscopically and microscopically observed. The greater the impact energy, the greater the deformation of the upper skin and the more severe the compression and buckling of the middle honeycomb. Severe delamination damage occurred between the upper CFRP skin and the honeycomb aluminum, as shown by the red line in the figure. For the honeycomb aluminum sandwich structure with pure CFRP skin, when subjected to an impact energy of 15J, the upper CFRP skin suffered severe fiber breakage, while for the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, the upper CFRP skin did not suffer such severe damage. This is because the elastomer converts the local impact load into a global load, causing more material at a distance from the drop hammer to participate in the load-bearing.

[0138] like Figure 4As shown in the figure, under the impact energy of 10J, the upper skins of the two sandwich structures had slight delamination damage, and the elastomer had a good interface with the two adjacent layers of CFRP, and no debonding occurred. Under the impact energy of 15J, the upper skin of the honeycomb aluminum sandwich structure with pure CFRP skin suffered fiber breakage and severe delamination damage, while the upper skin of the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer had a lower level of damage, with only slight delamination damage occurring between different layers. The damage types observed in these micrographs are consistent with those shown in the load-displacement curves shown in the figure.

[0139] 3. Damage Assessment

[0140] The main reason for the differences in the load-time curves, load-displacement curves and energy-time curves of the two structures in the invention in the low-speed impact test and simulation results is the change in the internal damage mechanism after the elastomer layer is introduced. In the evaluation method of this project, the main influencing factors that cause the difference are evaluated. It includes four aspects: plastic deformation and yielding of honeycomb aluminum, matrix failure, fiber breakage and delamination damage. It should be noted that the delamination here is not only the delamination between the orthogonal fiber layers inside the carbon fiber skin, but also the delamination between the CFRP skin and the honeycomb aluminum core.

[0141] like Figure 5a , 5b As shown in the figure, the plastic deformation and energy absorption of honeycomb aluminum during low-speed impact is one of the main energy absorption mechanisms. According to the experimental and simulation results, this part of energy increases slowly at the beginning of the impact, and increases rapidly when the displacement exceeds 3mm, and remains unchanged during the process of reaching the maximum displacement rebound. In this process, due to the high fracture toughness of honeycomb aluminum, its plastic energy-displacement curve is smoother and has no oscillation.

[0142] Comparing the plastic energy-displacement curves of the two materials, the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer increases the energy absorbed by the deformation of the honeycomb aluminum: the honeycomb aluminum plastic energy of the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer accounts for 36% of the total energy absorption, while the honeycomb aluminum sandwich core structure with pure CFRP skin only accounts for 29%.

[0143] like Figure 6aAs shown in the figure, for the honeycomb aluminum sandwich structure with pure CFRP skin, the matrix of the upper CFRP skin cracked, causing the load to oscillate, and the first load dropped to about 1270N. At a displacement of about 4.5mm, the load peak reached about 3100N. This sharp drop in load was due to serious damage to the upper CFRP skin, including large-area matrix damage and catastrophic fiber breakage. At the same time, large-area delamination damage occurred between different CFRP layers, exacerbating the steep drop phenomenon. For the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, after reaching the peak load, it did not experience large-area matrix cracking and fiber breakage like the honeycomb aluminum sandwich structure with pure CFRP skin, so the load did not drop sharply.

[0144] This is because the introduction of the elastomer makes the impact load more evenly distributed on the upper skin, allowing the CFRP in the area farther from the drop weight to participate in the load-bearing. Compared with the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, the matrix energy dissipation in the honeycomb aluminum sandwich core structure of pure CFRP skin is 78% higher. At the same time, judging from the amount of energy absorbed by the destruction between the orthogonal CFRP layers, the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer is significantly smaller than the honeycomb aluminum sandwich core structure of pure CFRP skin. Therefore, the introduction of the elastomer increases the toughness of the upper skin, effectively improves the use efficiency of CFRP, protects the integrity of the layers between different CFRP layers, and improves the impact resistance of the sandwich structure.

[0145] As shown in Figure 7, it can be seen that the delamination between the 0° and 90°F FRP interfaces of the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer is significantly less than that of the CFRP honeycomb aluminum sandwich structure with pure CFRP skin, while the delamination between the upper skin and the honeycomb aluminum is just the opposite, with the former being much greater than the latter. By comparison, it can be seen that the introduction of the elastomer layer has a positive effect on reducing delamination of the material in low-speed impact.

[0146] The energy dissipated by the damage in the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer is significantly higher than that in the honeycomb aluminum sandwich structure with pure CFRP skin. Matrix damage is the main form of energy dissipation in the carbon fiber layer, such as Figure 8a , 8b As shown in the figure, the matrix stretching starting criterion HSNMTCRT value is as follows: Figure 8a, red indicates the total amount of matrix damage, and blue indicates the undamaged area. The matrix cracking area of ​​each layer in the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer is larger than the matrix cracking area in the honeycomb aluminum sandwich structure with a pure CFRP skin. From the perspective of each layer, the matrix damage is more dispersed rather than concentrated in the local area around the impactor. This is because the introduction of the elastomer makes the stress more evenly distributed in the upper CFRP panel. The fibers that are the main load-bearing do not suffer from severe fracture damage like the pure CFRP skin sandwich structure, ensuring the structural integrity of the upper panel. More matrix farther away from the hammer head participates in dissipating energy, such as Figure 8c As shown in the figure, the energy dissipated by each CFRP layer in the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer is higher than that in the pure CFRP skin sandwich structure.

[0147] 4. Energy evaluation during impact

[0148] During the impact process, the kinetic energy of the impactor is mainly transferred to the sandwich structure through damage energy and elastic strain energy. Fig. 9 As shown in the figure, the energy changes of the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer and the pure CFRP-honeycomb aluminum sandwich structure during the 15J impact process were studied. The upper skin and honeycomb aluminum are the main objects of energy transfer of the impactor. When the elastomer is introduced, the energy stored in the upper CFRP skin at the peak value increases by 28%. Due to the introduction of the elastomer, the load is further dispersed, the CFRP participates more in the overall deformation process, and the fiber will not break. For the interface between the CFRP layers, the introduction of the elastomer layer greatly reduces the proportion of its absorbed energy. In the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, the peak energy stored at the interface between the CFRP layer and the elastomer is about 67% of the energy stored at the interface of the CFRP layer in the pure CFRP-honeycomb aluminum sandwich structure. This shows that the introduction of the elastomer improves the interface performance between the 0℃ FRP and 90℃ FRP layers by changing the proportion of load-bearing materials. The main role of the elastomer during the impact process is not to store more energy, but to diffuse the local kinetic energy to the whole of the laminate. In summary, the elastomer layer improves the overall bearing capacity of the sandwich structure by changing the energy distribution between the components during the impact.

[0149] For honeycomb aluminum, thanks to the large-area deformation of the upper CFRP panel, the energy absorption peak of the honeycomb aluminum in the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer is 8% higher than that of the honeycomb aluminum in the pure CFRP-honeycomb aluminum sandwich structure. At the same time, the energy finally dissipated by the honeycomb aluminum is close to the energy absorption peak during the impact process. This is because the thickness of the honeycomb aluminum is relatively thin, and the deformation produced during the impact process is mostly plastic deformation. For CFRP, in addition to irreversible damage deformation, there is also elastic deformation during the impact process. From the lowest point of the falling hammer to the end of the impact, the elastic energy is returned to the hammer head, and the elastic deformation is restored. The difference between CFRP and honeycomb aluminum in recoverable deformation explains the phenomenon of large-area stratification at the interface between CFRP and honeycomb aluminum.

[0150] Research on energy distribution during impact shows that the CFRP-honeycomb aluminum sandwich structure with the introduction of an elastomer layer can disperse the load more, improve the toughness of the skin, change the energy distribution, mobilize the overall bearing capacity of the material to participate in energy absorption, and improve its impact resistance.

[0151] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, characterized in that: include: An elastomer is inserted between the 0°CFRP and the 90°CFRP of different layers of the upper skin or / and between the 0°CFRP and the 90°CFRP of different layers of the lower skin in the CFRP-honeycomb aluminum; the elastomer is an ethylene propylene diene monomer rubber elastomer; The method for preparing the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer comprises the following steps: Step 1, using unidirectional CFRP prepreg to orthogonally lay up the upper skin and the lower skin, in the process of laying up the upper skin and the lower skin, inserting an elastomer between the 0°CFRP and the 90°CFRP of different layers of the upper skin or / and between the 0°CFRP and the 90°CFRP of different layers of the lower skin as needed; Step 2, curing the skin with the elastomer inserted separately; Step 3: Connect the cured skin, the honeycomb aluminum core and the uncured skin by means of an epoxy resin film and then cure them to obtain the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer.

2. The CFRP-honeycomb aluminum sandwich structure containing an elastomer layer according to claim 1, characterized in that: An elastomer is inserted between the second CFRP layer and the third CFRP layer and between the fifth CFRP layer and the sixth CFRP layer of the upper skin in the CFRP-honeycomb aluminum.

3. A method for evaluating the performance of a CFRP-honeycomb aluminum sandwich structure containing an elastomer layer, characterized in that: Using the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer as claimed in claim 2 comprises the following steps: Step 1, performing multiple groups of energy impact preliminary experiments on the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer and the pure CFRP-honeycomb aluminum sandwich structure to determine the impact energy range; Step 2: performing a low-speed impact test on the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer within the impact energy range, and establishing a simulation model under low-speed impact; Step 3: Compare the experimental results of the simulation model and the low-speed impact test, obtain multiple performance parameters, determine the feasibility of the simulation model, and perform performance evaluation on the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer according to the performance parameters; In the step 3, the performance parameters include a load history curve, a macroscopic image after impact, a microscopic image after impact, a plastic energy-displacement curve, a crack energy-displacement curve, a delamination image after impact, an intra-layer damage image after impact, and an energy distribution curve during impact; The load history curve includes a load-time curve, a load-displacement curve and an energy-time curve; The post-impact intra-layer damage image includes matrix failure images of different plies of the CFRP panel after impact and energy dissipation images of different CFRP plies.

4. The performance evaluation method of the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer according to claim 3, characterized in that: The impact energy range is 8J~15J.

5. The performance evaluation method of the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer according to claim 3, characterized in that: The low-speed impact test in step 2 includes the following process: clamping the sample to be impacted in a fixture, and using an impactor with a spherical hammer head mass of 5 kg and a spherical hammer head diameter of 16 mm to impact the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer with a preset energy; The preset energies include 10J and 15J, and the impact speed is no more than 3.4m / s.

6. The performance evaluation method of the CFRP-honeycomb aluminum sandwich structure containing an elastomer layer according to claim 3, characterized in that: In step 3, the performance evaluation includes: The onset of damage to the CFRP-aluminum honeycomb sandwich structure containing the elastomer layer is evaluated by the appearance of oscillations in the load history curve; In the macroscopic image after the impact, the impact energy is evaluated by the deformation of the upper skin and the degree of compression and buckling of the middle honeycomb aluminum; evaluating the impact energy by the damage of the upper skin in the microscopic image after the impact; The fracture condition of the honeycomb aluminum in the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer is evaluated by the appearance of a steep drop in the plastic energy-displacement curve; The fracture condition of the upper skin in the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer is evaluated by the appearance of a steep drop in the crack energy-displacement curve; Determining and evaluating the effect of introducing the elastomer into the CFRP-honeycomb aluminum sandwich structure containing the elastomer layer on reducing the delamination by the delamination condition in the delamination image after the impact; evaluating the degree of matrix damage by the ratio of matrix cracking areas in the matrix failure images of different plies of the CFRP panel after impact and the energy dissipation images of the different CFRP plies; The overall load-bearing capacity is evaluated by the energy distribution in the energy distribution curve during the impact.

Citation Information

Patent Citations

  • Composite honeycomb sandwich structure floor

    CN102080439A

  • Honeycomb sandwich panel

    JP1999129364A